Update: Is exercise-induced oxidative stress a friend or foe? - Powers, S. K.; Gomez-Cabrera, M. C (Sports Medicine and Health Science, 2026)
Free radicals (radicals) are highly reactive atoms or molecules that contain one or more unpaired electrons in their outermost shell. The first evidence that muscular exercise increases radical production and promotes oxidative damage to tissues was reported almost five decades ago. Following this milestone discovery, many studies have corroborated the finding that exercise increases the production of radicals and other reactive oxygen species (ROS) resulting in oxidative damage to macromolecules in muscles and other tissues. Although exercise-induced ROS production is associated with oxidative damage in many tissues, growing evidence reveals that ROS produced in contracting muscles act as signaling molecules to promote healthy exercise-induced adaptations in skeletal muscles and other tissues. These adaptive responses include increased mitochondrial volume, improved antioxidant capacity, and expression of cytoprotective proteins. Therefore, a key question emerges: "Is exercise-induced ROS production a friend or foe?" This review provides a state-of-the-art discussion of both the positive and negative effects of exercise-induced ROS production by examining the consequences of both oxidative damage to cellular macromolecules and the redox signaling-induced adaptations that occur in muscle fibers. To address the question of whether exercise-induced ROS production is a friend or foe we conclude with a risk/benefit analysis of the biological effects of exercise-induced production of ROS.